Inorganic nano mineral powder modified silicon-based floor coating and preparation method thereof

By combining modified nano-mineral powder with base paint, the problem of short service life and insufficient durability of floor coatings in high humidity and high load environments is solved, and the durability, chemical corrosion resistance and wear resistance of the coating are improved, and it meets modern environmental protection requirements.

CN119875501APending Publication Date: 2025-04-25CHANGZHOU HANCHAO ENVIRONMENTAL PROTECTION TECHNOLOGY CO LTD +1
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202510028915.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing floor coating has a short service life in high humidity and high load environments, and the water-based coating has insufficient durability and water resistance after film formation, and poor dispersion of nano-mineral powder and low economic benefits.

Method used

Modified nano-mineral powder is combined with base paint, and silica is modified by silane coupling agent, aluminum trioxide is modified and zirconium dioxide is modified by silane coupling agent, thereby improving the dispersion of nano-mineral powder and the performance of the coating.

Benefits of technology

It improves the dispersion and usage performance of the coating, enhances the durability, chemical corrosion resistance, wear resistance, adhesion and radiation resistance of the coating, reduces harmful gas emissions, and meets modern environmental protection requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119875501A_ABST
    Figure CN119875501A_ABST
Patent Text Reader

Abstract

The invention discloses an inorganic nano mineral powder modified silicon-based floor coating and a preparation method thereof, and belongs to the technical field of waterproof coatings. The inorganic nano mineral powder modified silicon-based floor coating is prepared from base paint, an alcohol dispersant and modified nano mineral powder, the ratio of the base paint to the modified nano mineral powder is 100 L: (0.1-1) kg, and the ratio of the base paint to the alcohol dispersing agent is 100 L: (1-3) kg; the basic paint is prepared from the following components in parts by mass: 30 to 40 parts of propylene glycol monomethyl ether, 20 to 30 parts of modified polysiloxane, 20 to 25 parts of a first alcohol organic solvent and 10 to 20 parts of water; the modified nano mineral powder is one or more of silane coupling agent modified silicon dioxide, silane coupling agent modified aluminum oxide and silane coupling agent modified zirconium dioxide. Due to the addition of the modified nano mineral powder, the dispersity of the nano mineral powder is improved, and the use performance of the coating is improved due to the matched use of the modified nano mineral powder and the basic paint.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of waterproof coatings, and more specifically to an inorganic nano-mineral powder-modified silicon-based floor coating and a preparation method thereof. Background Art

[0002] In order to avoid pollution and extend the service life of the floor in high humidity and high load environment, there are many floor coatings on the market. Their function is to reduce the surface roughness of the floor to reduce the friction coefficient and increase the surface hydrophobicity to solve the problem of plaster water resistance and wear resistance. Most of these coatings are solvent-based coatings. The organic solvents volatilized from the coating during the film formation process are mostly toxic and harmful substances, which not only harm the human body, but also pollute the natural environment. The durability and water resistance of environmentally friendly water-based coatings after film formation are also problems that need to be considered.

[0003] In view of these situations, the use of nano-mineral powder to modify water-based paint is a novel method. Nanoparticles can increase the hardness of the surface, increase the hydrophobicity of the material, and improve the wear resistance of the material without generating macroscopic roughness, thereby reducing the maintenance cost of the surface. For example, Chinese invention patent CN114702871A discloses a metal surface anti-oil nano-coating agent and its preparation method, which inspires the application of nano-mineral powder in floor coatings. Chinese invention patent CN110885615A discloses a water-based epoxy floor coating and its preparation method and construction method, in which 13wt% to 20wt% of nano-alumina is added. Chinese invention patent CN107903688A discloses a coating composition and its preparation method, which utilizes the interaction of different types of nano-mineral powders to improve the performance of the coating. Chinese invention patent CN109608984A discloses a water-based waterproof and anti-skid floor coating and its preparation method, which adds talcum powder, quartz powder and zirconium dioxide to improve the anti-skid performance of the coating.

[0004] However, in the above studies, a large amount of nano-mineral powder is used as a filler to enhance the strength of the coating and improve the anti-slip performance to a certain extent. However, if the amount of nano-mineral powder added is greater than 1wt%, the dispersion of the nano-mineral powder in the coating will be poor and the economic benefits will be low. Summary of the invention

[0005] In view of the above problems, the present invention provides a silicon-based floor coating modified with inorganic nano-mineral powder and a preparation method thereof. The present invention adds modified nano-mineral powder, which not only improves the dispersibility of the nano-mineral powder in the coating, but also the modified nano-mineral powder is used in combination with the base paint, which effectively improves the performance of the coating.

[0006] The first object of the present invention is to provide a silicon-based floor coating modified by inorganic nano-mineral powder, which is made of base paint, alcohol dispersant and modified nano-mineral powder; the ratio of base paint to modified nano-mineral powder is 100L:0.1kg-1kg, and the ratio of base paint to alcohol dispersant is 100L:1kg-3kg. For example, the ratio of base paint to modified nano-mineral powder is 100L:0.1kg, 100L:0.2kg, 100L:0.3kg, 100L:0.4kg, 100L:0.5kg, 100L:0.6kg, 100L:0.7kg, 100L:0.8kg, 100L:0.9kg or 100L:1kg, etc.; the volume ratio of base paint to alcohol dispersant is 100L:1kg, 100L:2kg or 100L:3kg, etc.

[0007] The base paint is prepared by polymerizing the following components in parts by mass: 30 to 40 parts of propylene glycol methyl ether, 20 to 30 parts of modified polysiloxane, 20 to 25 parts of a first alcohol organic solvent, and 10 to 20 parts of water.

[0008] For example, propylene glycol methyl ether is 30 parts, 31 parts, 32 parts, 33 parts, 34 parts, 35 parts, 36 parts, 37 parts, 38 parts, 39 parts or 40 parts, etc.

[0009] 20 parts, 21 parts, 22 parts, 23 parts, 24 parts, 25 parts, 26 parts, 27 parts, 28 parts, 29 parts or 30 parts of modified polysiloxane, etc.

[0010] The first alcohol organic solvent is 20 parts, 21 parts, 22 parts, 23 parts, 24 parts or 25 parts.

[0011] 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts or 20 parts of water, but are not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0012] The modified nano mineral powder is one or more of silicon dioxide modified by a silane coupling agent, aluminum oxide modified by a silane coupling agent, and zirconium dioxide modified by a silane coupling agent.

[0013] In a preferred embodiment of the present invention, the second alcohol organic solvent and water are used as the first mixed solvent, the first silane coupling agent is used as the modifier, nano-silica is added, and the silane coupling reaction occurs at 70°C to 90°C to obtain silane coupling agent modified silica. For example, the temperature for the silane coupling reaction is 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C, 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C or 90°C. More preferably, the time for the silane coupling reaction is 50min to 100min, for example, the time for the silane coupling reaction is 50min, 60min, 70min, 80min, 90min or 100min. More preferably, when preparing silane coupling agent modified silica, the volume ratio of the second alcohol organic solvent, water and the first silane coupling agent is 10:10:1-4, for example, the volume ratio of the second alcohol organic solvent, water and the first silane coupling agent is 10:10:1, 10:10:2, 10:10:3, 10:10:4, etc.; the ratio of nano-silica to the first silane coupling agent is 1g:1-4ml, for example, the ratio of nano-silica to the first silane coupling agent is 1g:1ml, 1g:2ml, 1g:3ml or 1g:4ml, etc., but it is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0014] In a preferred embodiment of the present invention, a third alcohol organic solvent and water are used as the second mixed solvent, a second silane coupling agent is used as a modifier, nano aluminum oxide is added, and a silane coupling reaction occurs at 70°C to 90°C to obtain silane coupling agent modified aluminum oxide. For example, the temperature for the silane coupling reaction is 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C, 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C or 90°C. More preferably, the time for the silane coupling reaction is 50min to 100min, for example, the time for the silane coupling reaction is 50min, 60min, 70min, 80min, 90min or 100min. More preferably, when preparing silane coupling agent modified aluminum oxide, the volume ratio of the third alcohol organic solvent, water and the second silane coupling agent is 10:10:1-4, for example, the volume ratio of the third alcohol organic solvent, water and the second silane coupling agent is 10:10:1, 10:10:2, 10:10:3, 10:10:4, etc.; the ratio of nano aluminum oxide to the second silane coupling agent is 1g:1-4ml, for example, the ratio of nano aluminum oxide to the second silane coupling agent is 1g:1ml, 1g:2ml, 1g:3ml or 1g:4ml, etc. However, it is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0015] In a preferred embodiment of the present invention, a fourth alcohol organic solvent and water are used as a third mixed solvent, a third silane coupling agent is used as a modifier, nano zirconium dioxide is added, and a silane coupling reaction occurs at 70°C to 90°C to obtain silane coupling agent modified zirconium dioxide. For example, the temperature for the silane coupling reaction is 70°C, 71°C, 72°C, 73°C, 74°C, 75°C, 76°C, 77°C, 78°C, 79°C, 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C or 90°C. More preferably, the time for the silane coupling reaction is 50min to 100min, for example, the time for the silane coupling reaction is 50min, 60min, 70min, 80min, 90min or 100min. More preferably, when preparing silane coupling agent modified zirconium dioxide, the volume ratio of the fourth alcohol organic solvent, water and the third silane coupling agent is 10:10:1-4, for example, the volume ratio of the fourth alcohol organic solvent, water and the third silane coupling agent is 10:10:1, 10:10:2, 10:10:3, 10:10:4, etc.; the ratio of nano zirconium dioxide to the third silane coupling agent is 1g:1-4ml, for example, the ratio of nano zirconium dioxide to the third silane coupling agent is 1g:1ml, 1g:2ml, 1g:3ml or 1g:4ml, etc., but it is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0016] In a preferred embodiment of the present invention, the particle sizes of silicon dioxide, aluminum oxide and zirconium dioxide are all 10 nm to 100 nm.

[0017] In a preferred embodiment of the present invention, the alcohol dispersant is polyethylene glycol.

[0018] In a preferred embodiment of the present invention, the first silane coupling agent is KH550 or KH560, the second silane coupling agent is KH550 or KH560, and the third silane coupling agent is KH550 or KH560.

[0019] The second object of the present invention is to provide a method for preparing the above-mentioned inorganic nano-mineral powder modified silicon-based floor coating, comprising the following steps: weighing the components of the base paint according to the following mass parts: 30 to 40 parts of propylene glycol methyl ether, 20 to 30 parts of modified polysiloxane, 20 to 25 parts of the first alcohol organic solvent, and 10 to 20 parts of water; after mixing water, the first alcohol organic solvent, propylene glycol methyl ether and the modified polysiloxane evenly, a polymerization reaction occurs to obtain a base paint. According to the ratio of the base paint to the modified nano-mineral powder of 100mL:0.1g to 1g, and the volume ratio of the base paint to the alcohol dispersant of 100:1 to 1.2, weigh the base paint, the alcohol dispersant and the modified nano-mineral powder, and mix the modified nano-mineral powder, the base paint and the alcohol dispersant evenly to obtain the inorganic nano-mineral powder modified silicon-based floor coating.

[0020] In a preferred embodiment of the present invention, the reaction temperature of the polymerization reaction is 20°C to 30°C, for example, the reaction temperature is 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C, 29°C or 30°C, etc., but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0021] The reaction time is 5 h to 7 h, for example, the reaction time is 5 h, 5.5 h, 6 h, 6.5 h or 7 h, etc., but is not limited to the listed values, and other unlisted values ​​within the above numerical range are also applicable.

[0022] In a preferred embodiment of the present invention, when mixing to obtain a silicon-based floor coating modified with inorganic nano-mineral powder, the mixing temperature is 15°C to 30°C, and the mixing temperature is 15°C, 16°C, 17°C, 18°C, 19°C, 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C, 29°C or 30°C, etc.

[0023] The mixing time is 15 min to 45 min, for example, the mixing time is 15 min, 20 min, 25 min, 30 min, 35 min, 40 min or 45 min, etc., but is not limited to the listed values, and other values ​​not listed within the above numerical range are also applicable.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] (1) Compared with the prior art, the present invention adds modified nano-mineral powder, and the modified nano-mineral powder is modified by a silane coupling agent to improve the dispersibility of the nano-mineral powder. After adding a relatively low content of modified nano-mineral powder in the ratio of 100mL:0.1g to 1g of the base paint and the modified nano-mineral powder, the amino group in the modified nano-mineral powder will undergo nucleophilic attack with the carbon atom in the silane in the presence of propylene glycol methyl ether, and a C=N double bond will be formed after the water molecule is removed. The formation of the C=N double bond may improve the chemical stability of the coating, and enhance the durability and chemical erosion resistance of the coating. The inlay of low-content modified nano-mineral powder can refine the grains and form a more wear-resistant coating structure. A small amount of mineral powder grains and coating crystal dislocation accumulation also play a role in strengthening the coating. In addition, the addition of modified nano-mineral powder can make the paint film form a denser structure and a lower water absorption rate to improve the adhesion, wear resistance, impact resistance, flexibility, corrosion resistance and radiation resistance of the floor coating. The addition of nano-scale particles can make floor materials more suitable for places with long-term and high-intensity use.

[0026] (2) The high-strength silicon-based floor coating modified with low-amount inorganic nano-mineral powder prepared by the present invention has better tolerance, chemical corrosion resistance, flexibility, elasticity and hydrophobicity than ordinary epoxy resin coatings, and can ensure the integrity of the coating under various environments.

[0027] (3) The high-strength silicon-based floor coating modified with low-amount inorganic nano-mineral powder prepared by the present invention has good dispersibility, high economic benefits, strong performance improvement effect, small impact on the environment, reduced emission of harmful gases, and meets modern environmental protection requirements.

[0028] (4) The high-strength silicon-based floor coating modified with low-amount inorganic nano-mineral powder prepared by the present invention has good leveling and coating properties and is easy to construct and operate. Among them, any one or more of the three modified nano-mineral powders of silane coupling agent modified silicon dioxide, silane coupling agent modified aluminum oxide and silane coupling agent modified zirconium dioxide can be completely and evenly dispersed in the coating at a low dosage without agglomeration, precipitation and the like.

[0029] (5) The addition of a small amount of nanoparticles can also improve the surface smoothness and texture of floor coatings, making them more uniform and delicate, which helps to achieve a higher decorative effect, which is especially important for commercial and residential places that require high aesthetics.

[0030] (6) The present invention improves the various properties of the floor protective surface layer by developing a high-strength silicon-based floor coating modified with a low amount of inorganic nano-mineral powder, thereby improving the quality of the floor material. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is the SEM image of the coating in Example 2.

[0032] Figure 2 The SEM and EDS images of various element distributions of the coating in Example 2, wherein (a) is the SEM image of the coating surface, (b) is the O element distribution image, (c) is the C element distribution image, and (d) is the Si element distribution image.

[0033] Figure 3 The SEM and EDS images of various element distributions of the coating in Example 6, wherein (a) is the SEM image of the coating surface, (b) is the O element distribution image, (c) is the C element distribution image, and (d) is the Al element distribution image.

[0034] Figure 4 This is a graph showing the wear resistance coefficient of the coating in Example 2.

[0035] Figure 5 This is a graph showing the wear resistance coefficient of the coating in Example 3. DETAILED DESCRIPTION

[0036] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] In the process of raw material selection and matching of inorganic nano-mineral powder modified silicon-based floor coating, multiple factors such as raw material physical and chemical properties, functional additives, coating performance, environmental protection and economy are comprehensively considered. Select nano-mineral powder with high Mohs hardness, ability to increase bending and compression resistance, strong coupling with coating materials, good dispersibility and only low dosage to achieve the performance improvement of coating. According to the characteristics of each nano-mineral powder, reasonable raw material matching and ratio optimization can significantly improve the performance of floor coating and meet the needs of practical applications. Specifically, the present invention provides an inorganic nano-mineral powder modified silicon-based floor coating, which is made of base paint, alcohol dispersant and modified nano-mineral powder; the ratio of base paint to modified nano-mineral powder is 100L: 0.1kg~1kg, and the ratio of base paint to alcohol dispersant is 100L: 1kg~3kg.

[0038] The base paint consists of the following components in parts by mass: 30-40 parts of propylene glycol methyl ether, 20-30 parts of modified polysiloxane, 20-25 parts of the first alcohol organic solvent, and 10-20 parts of water.

[0039] The modified nano mineral powder is one or more of silicon dioxide modified by a silane coupling agent, aluminum oxide modified by a silane coupling agent, and zirconium dioxide modified by a silane coupling agent.

[0040] After mixing the raw materials used in the base paint, these silanes can enhance the heat resistance, chemical resistance and adhesion of the paint by forming a siloxane network. When adding modified nano-mineral powder to the base paint, the modified nano-mineral powder can refine the grains and form a more wear-resistant coating structure. A small amount of mineral powder grains and coating crystal dislocation accumulation also play a role in strengthening the coating. The addition of alcohol dispersants can increase the stability of the suspension and accelerate the dispersion efficiency.

[0041] It should be noted that the molecular weight of the polysiloxane used in the present invention is 8000 g / mol, and it was purchased from Sinopharm Chemical Reagent Co., Ltd. The alcohol dispersant used in the embodiments of the present invention is polyethylene glycol, and the molecular weight is 650. KH550 refers to γ-aminopropyltriethoxysilane.

[0042] Example 1

[0043] This embodiment provides a method for preparing a high-strength silicon-based floor coating modified with a low amount of inorganic nano-mineral powder, comprising the following steps:

[0044] (1) Deionized water, anhydrous ethanol, modified polysiloxane and propylene glycol methyl ether were weighed in a mass ratio of 15:21.8:24.5:38.7, mixed, ultrasonically dispersed for about 30 minutes, added to a round-bottom flask equipped with a magnetic stirring bar, and stirred at 25° C. for 5 hours to obtain a base paint.

[0045] (2) SiO2, KH550, anhydrous ethanol and deionized water with a particle size of 20 nm were weighed in a ratio of 1 g: 1 ml: 10 ml: 10 ml, and the SiO2, KH550, anhydrous ethanol and deionized water with a particle size of 20 nm were mixed and ultrasonically dispersed for 20 min to prepare a nano-mineral powder suspension, and heated and shaken in a constant temperature shaking incubator at 200 rpm and 80° C. for 1 h. After the reaction was completed, centrifugal washing was performed, and the mixture was washed with anhydrous ethanol for 3 times to remove the unreacted silane coupling agent. Then, the silane coupling agent-modified silica was obtained by drying in an oven at 65° C., and ground and sealed for later use.

[0046] (3) Silane coupling agent-modified silica, alcohol dispersant and base paint were weighed in a ratio of 0.1 g: 1 g: 100 ml, mixed and ultrasonically dispersed at 25° C. for 20 min to obtain an inorganic nano-mineral powder-modified silicon-based floor coating.

[0047] Example 2

[0048] This embodiment provides a method for preparing a high-strength silicon-based floor coating modified with a low amount of inorganic nano-mineral powder, comprising the following steps:

[0049] (1) Deionized water, anhydrous ethanol, modified polysiloxane and propylene glycol methyl ether were weighed in a mass ratio of 15:21.8:24.5:38.7, mixed, ultrasonically dispersed for about 30 minutes, added to a round-bottom flask equipped with a magnetic stirring bar, and stirred at 25° C. for 5 hours to obtain a base paint.

[0050] (2) SiO2, KH550, anhydrous ethanol and deionized water with a particle size of 20 nm were weighed in a ratio of 1 g: 1 ml: 10 ml: 10 ml, and the SiO2, KH550, anhydrous ethanol and deionized water with a particle size of 20 nm were mixed and ultrasonically dispersed for 20 min to prepare a nano-mineral powder suspension, and heated and shaken in a constant temperature shaking incubator at 200 rpm and 80° C. for 1 h. After the reaction was completed, centrifugal washing was performed, and the mixture was washed with anhydrous ethanol for 3 times to remove the unreacted silane coupling agent. Then, the silane coupling agent-modified silica was obtained by drying in an oven at 65° C., and ground and sealed for later use.

[0051] (3) Silane coupling agent-modified silica, alcohol dispersant and base paint were weighed in a ratio of 0.5 g: 1 g: 100 ml, mixed and ultrasonically dispersed at 25° C. for 20 min to obtain an inorganic nano-mineral powder-modified silicon-based floor coating.

[0052] Example 3

[0053] This embodiment provides a method for preparing a high-strength silicon-based floor coating modified with a low amount of inorganic nano-mineral powder, comprising the following steps:

[0054] (1) Deionized water, anhydrous ethanol, modified polysiloxane and propylene glycol methyl ether were weighed in a mass ratio of 15:21.8:24.5:38.7, mixed, ultrasonically dispersed for about 30 minutes, added to a round-bottom flask equipped with a magnetic stirring bar, and stirred at 25° C. for 5 hours to obtain a base paint.

[0055] (2) SiO2, KH550, anhydrous ethanol and deionized water with a particle size of 20 nm were weighed in a ratio of 1 g: 1 ml: 10 ml: 10 ml, and the SiO2, KH550, anhydrous ethanol and deionized water with a particle size of 20 nm were mixed and ultrasonically dispersed for 20 min to prepare a nano-mineral powder suspension, and heated and shaken in a constant temperature shaking incubator at 200 rpm and 80° C. for 1 h. After the reaction was completed, centrifugal washing was performed, and the mixture was washed with anhydrous ethanol for 3 times to remove the unreacted silane coupling agent. Then, the silane coupling agent-modified silica was obtained by drying in an oven at 65° C., and ground and sealed for later use.

[0056] (3) Silane coupling agent-modified silica, alcohol dispersant and base paint were weighed in a ratio of 1 g: 1 g: 100 ml, mixed and ultrasonically dispersed at 25° C. for 20 min to obtain an inorganic nano-mineral powder-modified silicon-based floor coating.

[0057] Example 4

[0058] This embodiment provides a method for preparing a high-strength silicon-based floor coating modified with a low amount of inorganic nano-mineral powder, comprising the following steps:

[0059] (1) Deionized water, anhydrous ethanol, modified polysiloxane and propylene glycol methyl ether were weighed in a mass ratio of 15:21.8:24.5:38.7, mixed, ultrasonically dispersed for about 30 minutes, added to a round-bottom flask equipped with a magnetic stirring bar, and stirred at 25° C. for 5 hours to obtain a base paint.

[0060] (2) Al2O3, KH550, anhydrous ethanol and deionized water with a particle size of 20 nm were weighed in a ratio of 1 g: 1 ml: 10 ml: 10 ml, and the Al2O3, KH550, anhydrous ethanol and deionized water with a particle size of 20 nm were mixed and ultrasonically dispersed for 20 min to prepare a nano-mineral powder suspension, and heated and shaken in a constant temperature shaking incubator at 200 rpm and 80° C. for 1 h. After the reaction was completed, centrifugal washing was performed, and the mixture was washed with anhydrous ethanol for 3 times to remove the unreacted silane coupling agent. Then, the mixture was dried in an oven at 65° C. to obtain silane coupling agent-modified aluminum oxide, which was ground and sealed for later use.

[0061] (3) Silane coupling agent-modified aluminum oxide, alcohol dispersant and base paint were weighed in a ratio of 0.1 g: 1 g: 100 ml, mixed and ultrasonically dispersed at 25° C. for 20 min to obtain an inorganic nano-mineral powder-modified silicon-based floor coating.

[0062] Example 5

[0063] This embodiment provides a method for preparing a high-strength silicon-based floor coating modified with a low amount of inorganic nano-mineral powder, comprising the following steps:

[0064] (1) Deionized water, anhydrous ethanol, modified polysiloxane and propylene glycol methyl ether were weighed in a mass ratio of 15:21.8:24.5:38.7, mixed, ultrasonically dispersed for about 30 minutes, added to a round-bottom flask equipped with a magnetic stirring bar, and stirred at 25° C. for 5 hours to obtain a base paint.

[0065] (2) Al2O3, KH550, anhydrous ethanol and deionized water with a particle size of 20 nm were weighed in a ratio of 1 g: 1 ml: 10 ml: 10 ml, and the Al2O3, KH550, anhydrous ethanol and deionized water with a particle size of 20 nm were mixed and ultrasonically dispersed for 20 min to prepare a nano-mineral powder suspension, and heated and shaken in a constant temperature shaking incubator at 200 rpm and 80° C. for 1 h. After the reaction was completed, centrifugal washing was performed, and the mixture was washed with anhydrous ethanol for 3 times to remove the unreacted silane coupling agent. Then, the mixture was dried in an oven at 65° C. to obtain silane coupling agent-modified aluminum oxide, which was ground and sealed for later use.

[0066] (3) Silane coupling agent-modified aluminum oxide, alcohol dispersant and base paint were weighed in a ratio of 0.5 g: 1 g: 100 ml, mixed and ultrasonically dispersed at 25° C. for 20 min to obtain an inorganic nano-mineral powder-modified silicon-based floor coating.

[0067] Example 6

[0068] This embodiment provides a method for preparing a high-strength silicon-based floor coating modified with a low amount of inorganic nano-mineral powder, comprising the following steps:

[0069] (1) Deionized water, anhydrous ethanol, modified polysiloxane and propylene glycol methyl ether were weighed in a mass ratio of 15:21.8:24.5:38.7, mixed, ultrasonically dispersed for about 30 minutes, added to a round-bottom flask equipped with a magnetic stirring bar, and stirred at 25° C. for 5 hours to obtain a base paint.

[0070] (2) Al2O3, KH550, anhydrous ethanol and deionized water with a particle size of 20 nm were weighed in a ratio of 1 g: 1 ml: 10 ml: 10 ml, and the Al2O3, KH550, anhydrous ethanol and deionized water with a particle size of 20 nm were mixed and ultrasonically dispersed for 20 min to prepare a nano-mineral powder suspension, and heated and shaken in a constant temperature shaking incubator at 200 rpm and 80° C. for 1 h. After the reaction was completed, centrifugal washing was performed, and the mixture was washed with anhydrous ethanol for 3 times to remove the unreacted silane coupling agent. Then, the mixture was dried in an oven at 65° C. to obtain silane coupling agent-modified aluminum oxide, which was ground and sealed for later use.

[0071] (3) Silane coupling agent-modified aluminum oxide, alcohol dispersant and base paint were weighed in a ratio of 1 g: 1 g: 100 ml, mixed and ultrasonically dispersed at 25° C. for 20 min to obtain an inorganic nano-mineral powder-modified silicon-based floor coating.

[0072] Example 7

[0073] This embodiment provides a method for preparing a high-strength silicon-based floor coating modified with a low amount of inorganic nano-mineral powder, comprising the following steps:

[0074] (1) Deionized water, anhydrous ethanol, modified polysiloxane and propylene glycol methyl ether were weighed in a mass ratio of 15:21.8:24.5:38.7, mixed, ultrasonically dispersed for about 30 minutes, added to a round-bottom flask equipped with a magnetic stirring bar, and stirred at 25° C. for 5 hours to obtain a base paint.

[0075] (2) Weigh ZrO2, KH550, anhydrous ethanol and deionized water with a particle size of 20 nm in a ratio of 1 g: 1 ml: 10 ml: 10 ml, mix ZrO2, KH550, anhydrous ethanol and deionized water with a particle size of 20 nm, and then ultrasonically disperse them for 20 min to prepare a nano-mineral powder suspension, and heat and shake the suspension in a constant temperature shaking incubator at 200 rpm and 80° C. for 1 h. After the reaction is completed, centrifuge and wash the suspension, and then wash the suspension with anhydrous ethanol for 3 times to remove the unreacted silane coupling agent. Then dry the suspension in an oven at 65° C. to obtain silane coupling agent-modified zirconium dioxide, grind and seal the suspension for later use.

[0076] (3) Silane coupling agent-modified zirconium dioxide, alcohol dispersant and base paint were weighed in a ratio of 0.1 g: 1 g: 100 ml, mixed and ultrasonically dispersed at 25° C. for 20 min to obtain an inorganic nano-mineral powder-modified silicon-based floor coating.

[0077] Example 8

[0078] This embodiment provides a method for preparing a high-strength silicon-based floor coating modified with a low amount of inorganic nano-mineral powder, comprising the following steps:

[0079] (1) Deionized water, anhydrous ethanol, modified polysiloxane and propylene glycol methyl ether were weighed in a mass ratio of 15:21.8:24.5:38.7, mixed, ultrasonically dispersed for about 30 minutes, added to a round-bottom flask equipped with a magnetic stirring bar, and stirred at 25° C. for 5 hours to obtain a base paint.

[0080] (2) Weigh ZrO2, KH550, anhydrous ethanol and deionized water with a particle size of 20 nm in a ratio of 1 g: 1 ml: 10 ml: 10 ml, mix ZrO2, KH550, anhydrous ethanol and deionized water with a particle size of 20 nm, and then ultrasonically disperse them for 20 min to prepare a nano-mineral powder suspension, and heat and shake the suspension in a constant temperature shaking incubator at 200 rpm and 80° C. for 1 h. After the reaction is completed, centrifuge and wash the suspension, and then wash the suspension with anhydrous ethanol for 3 times to remove the unreacted silane coupling agent. Then dry the suspension in an oven at 65° C. to obtain silane coupling agent-modified zirconium dioxide, grind and seal the suspension for later use.

[0081] (3) Weigh silane coupling agent-modified zirconium dioxide, alcohol dispersant and base paint in a ratio of 0.5 g: 1 g: 100 ml, mix them and ultrasonically disperse them at 25° C. for 20 minutes to obtain an inorganic nano-mineral powder-modified silicon-based floor coating.

[0082] Example 9

[0083] This embodiment provides a method for preparing a high-strength silicon-based floor coating modified with a low amount of inorganic nano-mineral powder, comprising the following steps:

[0084] (1) Deionized water, anhydrous ethanol, modified polysiloxane and propylene glycol methyl ether were weighed in a mass ratio of 15:21.8:24.5:38.7, mixed, ultrasonically dispersed for about 30 minutes, added to a round-bottom flask equipped with a magnetic stirring bar, and stirred at 25° C. for 5 hours to obtain a base paint.

[0085] (2) Weigh ZrO2, KH550, anhydrous ethanol and deionized water with a particle size of 20 nm in a ratio of 1 g: 1 ml: 10 ml: 10 ml, mix ZrO2, KH550, anhydrous ethanol and deionized water with a particle size of 20 nm, and then ultrasonically disperse them for 20 min to prepare a nano-mineral powder suspension, and heat and shake the suspension in a constant temperature shaking incubator at 200 rpm and 80° C. for 1 h. After the reaction is completed, centrifuge and wash the suspension, and then wash the suspension with anhydrous ethanol for 3 times to remove the unreacted silane coupling agent. Then dry the suspension in an oven at 65° C. to obtain silane coupling agent-modified zirconium dioxide, grind and seal the suspension for later use.

[0086] (3) Weigh the silane coupling agent modified zirconium dioxide, alcohol dispersant and base paint in a ratio of 1 g: 1 g: 100 ml, mix them and ultrasonically disperse them at 25° C. for 20 minutes to obtain a silicon-based floor coating modified with inorganic nano-mineral powder.

[0087] Example 10

[0088] This embodiment provides a method for preparing a high-strength silicon-based floor coating modified with a low amount of inorganic nano-mineral powder, comprising the following steps:

[0089] (1) Deionized water, anhydrous ethanol, modified polysiloxane and propylene glycol methyl ether were weighed in a mass ratio of 15:21.8:24.5:38.7, mixed, ultrasonically dispersed for about 30 minutes, added to a round-bottom flask equipped with a magnetic stirring bar, and stirred at 25° C. for 5 hours to obtain a base paint.

[0090] (2) Weigh ZrO2, KH550, anhydrous ethanol and deionized water with a particle size of 20 nm in a ratio of 1 g: 1 ml: 10 ml: 10 ml, mix ZrO2, KH550, anhydrous ethanol and deionized water with a particle size of 20 nm, and then ultrasonically disperse them for 20 min to prepare a nano-mineral powder suspension, and heat and shake the suspension in a constant temperature shaking incubator at 200 rpm and 80° C. for 1 h. After the reaction is completed, centrifuge and wash the suspension, and then wash the suspension with anhydrous ethanol for 3 times to remove the unreacted silane coupling agent. Then dry the suspension in an oven at 65° C. to obtain silane coupling agent-modified zirconium dioxide, grind and seal the suspension for later use.

[0091] According to the ratio of 1g:1ml:10ml:10ml, weigh Al2O3, KH550, anhydrous ethanol and deionized water with a particle size of 20nm, mix Al2O3, KH550, anhydrous ethanol and deionized water with a particle size of 20nm, and then ultrasonically disperse them for 20min to prepare a nano-mineral powder suspension, and heat and shake the reaction in a constant temperature shaking incubator at 200rpm and 80℃ for 1h. After the reaction is completed, centrifugal washing is performed, and the unreacted silane coupling agent is washed 3 times with anhydrous ethanol to remove the unreacted silane coupling agent. Then, it is dried in an oven at 65℃ to obtain silane coupling agent modified aluminum oxide, which is ground and sealed for standby use.

[0092] According to the ratio of 1g:1ml:10ml:10ml, SiO2, KH550, anhydrous ethanol and deionized water with a particle size of 20nm were weighed, and the mixture was ultrasonically dispersed for 20min to prepare a nano-mineral powder suspension, and heated and shaken in a constant temperature shaking incubator at 200rpm and 80℃ for 1h. After the reaction was completed, centrifugal washing was performed, and the unreacted silane coupling agent was washed 3 times with anhydrous ethanol to remove the unreacted silane coupling agent. Then, the silane coupling agent-modified silica was dried in an oven at 65℃, and ground and sealed for later use.

[0093] (3) Silane coupling agent modified silica, silane coupling agent modified alumina, silane coupling agent modified zirconium dioxide, alcohol dispersant and base paint were weighed in a ratio of 0.5 g: 0.3 g: 0.1 g: 1 g: 100 ml, mixed and ultrasonically dispersed at 25 ° C for 20 minutes to obtain a composite inorganic nano-mineral powder modified silicon-based floor coating.

[0094] Comparative Example 1

[0095] In this comparative example, only the base paint is used as the floor coating. Deionized water, anhydrous ethanol, modified polysiloxane and propylene glycol methyl ether are weighed according to a mass ratio of 15:21.8:24.5:38.7, the deionized water, anhydrous ethanol, modified polysiloxane and propylene glycol methyl ether are mixed, ultrasonically dispersed for about 30 minutes, added to a round-bottom flask equipped with a magnetic stirring bar, and stirred at 25°C for 5 hours to obtain a base paint.

[0096] Figure 1 This is the SEM image of the ratio of silane coupling agent modified silica: alcohol dispersant: base paint of 0.5g:1ml:100ml. When the ratio of silane coupling agent modified silica: alcohol dispersant: base paint is 0.5g:1ml:100ml, SiO2 can be evenly dispersed in the coating, and the mineral powder does not agglomerate, with good dispersibility. Figure 2 In Example 6, 1wt% of nano-Al2O3 was dispersed in the coating, and the mineral powder also did not agglomerate, showing good dispersibility. Figure 3 shown.

[0097] The floor coatings prepared in Examples 1 to 10 and Comparative Example 1 were applied to the surface of the gypsum floor, the floor material was evenly brushed twice with putty, and the floor was roller-coated in three layers according to the primer, the middle coating, and the top coating, each layer of roller coating was applied 24 hours apart, and the coating was polished seven days after the third layer of roller coating was completed. The hardness of the gypsum floor coated with the floor coating was tested using a micro Vickers hardness tester.

[0098] The Vickers hardness test result of comparative example 1 is 492.2HV0.1. The wear resistance coefficient of the coating was tested by a multifunctional friction and wear test, wherein the wear resistance coefficient test result of comparative example 1 was 0.268. The water resistance, oil resistance, acid resistance, and alkali resistance of the coating were tested in accordance with GB / T22374-2018, wherein the test results of Examples 1 to 10 all met the requirements. Table 1 shows the Vickers hardness test results of the floor coating, and Table 2 shows the wear resistance coefficient test results of the floor coating. The lower the wear resistance coefficient, the better the wear resistance of the material. Table 3 shows the performance test results based on the requirements of GB / T 22374-2018.

[0099] Table 1 Vickers hardness test results

[0100] Test items Example 1 Example 2 Example 3 Example 4 Example 5 Vickers hardness / HV0.1 511.17 573.51 536.43 508.75 548.81 Test items Example 6 Example 7 Example 8 Example 9 Example 10 Vickers hardness / HV0.1 545.39 502.55 564.03 558.01 533.8

[0101] In the case of lack of nano-mineral powder in comparative example 1, the coating has poor performance in terms of hardness and wear resistance. According to Table 1, when different types of nano-mineral powder are added to Examples 1 to 10 of the present invention, the Vickers hardness of the coating increases to varying degrees. The reason should be attributed to the fact that the nano-mineral powder itself is a material with high hardness and can enhance the interaction between the paint molecules, thereby improving its resistance to external pressure. When the ratio of modified nano-mineral powder, alcohol dispersant and base paint exceeds 0.5g: 1ml: 100ml, the Vickers hardness of the coating will be reduced. This is because the addition of too high a concentration of nano-mineral powder may cause micro-agglomeration between the mineral powders, increasing the grain size of the mineral powder. To a certain extent, the larger the grain size, the lower the Vickers hardness of the coating. The Vickers hardness of the coating reaches the maximum value when the ratio of silane coupling agent modified silica: alcohol dispersant: base paint is 0.5g: 1ml: 100ml. It can be seen from Examples 1-10 that the use of silane coupling agent-modified silica as an added nano-mineral powder for silicon-based floor coatings can make the coating have a higher Vickers hardness. This may be due to the good physical dispersion of silane coupling agent-modified silica in the base paint. This good dispersion will lead to the accumulation of more mineral powder grains and coating crystal dislocations, ultimately strengthening the coating.

[0102] Table 2 Wear resistance coefficient test results

[0103]

[0104] Using metal balls as friction media, reciprocating friction tests were conducted on the composite coating of three mineral powders. The low wear coefficient of the material is manifested as high wear resistance. The essence of coating wear is the process in which the coating molecular chain is broken by shear and stretching of mechanical external forces. The higher the tensile strength of the resin molecular chain, the greater the interaction force, and the better its ability to resist external mechanical wear. The uniform dispersion of these three nano-mineral powders in the coating matrix is ​​conducive to their high tensile strength and long chain entanglement, thereby enhancing the wear resistance of the coating.

[0105] The average friction coefficients of different embodiments are shown in Table 2. The results show that the addition of the three modified nano-mineral powders improves the wear resistance of the coating. When the ratio of silane coupling agent modified silica: alcohol dispersant: base paint is 0.5g: 1g: 100ml, Figure 4The material shown has the lowest wear resistance coefficient. On the one hand, when the friction medium slips relative to the coating surface, the modified nano-mineral powder is embedded in the coating surface, reducing the direct contact between the friction medium and the coating surface. At the same time, the modified nano-mineral powder itself has super-hard and wear-resistant properties. On the other hand, the embedding of nano-mineral powder can refine the grains and form a more wear-resistant coating structure. When the ratio of modified nano-mineral powder: alcohol dispersant: base paint reaches 1g: 1g: 100ml, the wear resistance of the coating will be reduced. This may be due to the excessive amount of nano-mineral powder distributed in the coating matrix, which causes uneven surface roughness due to micro-agglomeration, thereby reducing the wear resistance of the coating. Figure 5 As shown. Example 10 simultaneously adds three kinds of nano-mineral powders, namely, silane coupling agent modified silicon dioxide, silane coupling agent modified aluminum oxide, and silane coupling agent modified zirconium dioxide. Although the hardness and wear resistance are slightly lower than those of Example 2, compared with a single nano-mineral powder, adding three kinds of nano-mineral powders, namely, silane coupling agent modified silicon dioxide, silane coupling agent modified aluminum oxide, and silane coupling agent modified zirconium dioxide, is more economical.

[0106] Table 3 Performance test results based on GB / T 22374-2018 requirements

[0107]

[0108] It can be seen from Table 3 that the inorganic nano-mineral powder-modified silicon-based floor coating prepared in the present invention can well meet the performance requirements of GB / T 22374-2018 in terms of water resistance, oil resistance, acid resistance and alkali resistance.

[0109] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0110] Obviously, those skilled in the art may make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A silicon-based floor coating modified by inorganic nano-mineral powder, characterized in that: It is made of base paint, alcohol dispersant and modified nano mineral powder; the ratio of base paint to modified nano mineral powder is 100L: 0.1kg-1kg, and the ratio of base paint to alcohol dispersant is 100L: 1kg-3kg; The base paint is prepared by polymerizing the following components in parts by weight: 30 to 40 parts of propylene glycol methyl ether, 20 to 30 parts of modified polysiloxane, 20 to 25 parts of a first alcohol organic solvent, and 10 to 20 parts of water; The modified nano mineral powder is one or more of silicon dioxide modified by a silane coupling agent, aluminum oxide modified by a silane coupling agent, and zirconium dioxide modified by a silane coupling agent.

2. The inorganic nano-mineral powder-modified silicon-based floor coating according to claim 1, characterized in that: The second alcohol organic solvent and water are used as the first mixed solvent, the first silane coupling agent is used as the modifier, nano silicon dioxide is added, and a silane coupling reaction occurs at 70° C. to 90° C. to obtain silane coupling agent modified silicon dioxide; the volume ratio of the second alcohol organic solvent, water and the first silane coupling agent is 10:10:1-4.

3. The inorganic nano-mineral powder-modified silicon-based floor coating according to claim 1, characterized in that: A third alcohol organic solvent and water are used as the second mixed solvent, a second silane coupling agent is used as a modifier, nano-aluminum oxide is added, and a silane coupling reaction occurs at 70° C. to 90° C. to obtain silane coupling agent-modified aluminum oxide; the volume ratio of the third alcohol organic solvent, water and the second silane coupling agent is 10:10:1-4.

4. The inorganic nano-mineral powder-modified silicon-based floor coating according to claim 1, characterized in that: A fourth alcohol organic solvent and water are used as the third mixed solvent, a third silane coupling agent is used as a modifier, nano zirconium dioxide is added, and a silane coupling reaction occurs at 70° C. to 90° C. to obtain silane coupling agent modified zirconium dioxide; the volume ratio of the fourth alcohol organic solvent, water and the third silane coupling agent is 10:10:1-4.

5. The inorganic nano-mineral powder-modified silicon-based floor coating according to claim 1, characterized in that: The particle sizes of silicon dioxide, aluminum oxide and zirconium dioxide are all between 10 nm and 100 nm.

6. The inorganic nano-mineral powder-modified silicon-based floor coating according to claim 1, characterized in that: The alcohol dispersant is polyethylene glycol.

7. The inorganic nano-mineral powder-modified silicon-based floor coating according to any one of claims 2 to 4, characterized in that: The first silane coupling agent is KH550 or KH560; The second silane coupling agent is KH550 or KH560; The third silane coupling agent is KH550 or KH560.

8. A method for preparing the inorganic nano-mineral powder modified silicon-based floor coating according to claim 1, characterized in that: The following steps are involved: Weigh the following components of the base paint in parts by weight: 30 to 40 parts of propylene glycol methyl ether, 20 to 30 parts of modified polysiloxane, 20 to 25 parts of the first alcohol organic solvent, and 10 to 20 parts of water; uniformly mix the water, the first alcohol organic solvent, propylene glycol methyl ether, and the modified polysiloxane, and perform a polymerization reaction to obtain a base paint; According to the ratio of base paint to modified nano-mineral powder of 100L:0.1kg~1kg, and the volume ratio of base paint to alcohol dispersant of 100:1~1.2, base paint, alcohol dispersant and modified nano-mineral powder are weighed, and the modified nano-mineral powder, base paint and alcohol dispersant are evenly mixed to obtain inorganic nano-mineral powder modified silicone-based floor coating.

9. The method for preparing a silicon-based floor coating modified by inorganic nano-mineral powder according to claim 8, characterized in that: The reaction temperature of the polymerization reaction is 20°C to 30°C, and the reaction time is 5h to 7h.

10. The method for preparing the inorganic nano-mineral powder-modified silicon-based floor coating according to claim 8, characterized in that: When the inorganic nano-mineral powder-modified silicon-based floor coating is obtained by mixing, the mixing temperature is 15° C. to 30° C., and the mixing time is 15 min to 45 min.

Citation Information

Patent Citations

  • Paint composition and preparation method thereof

    CN107903688A

  • Waterborne waterproof anti-slip floor coating and preparation method thereof

    CN109608984A

  • Waterborne epoxy floor coating and preparation method thereof, and construction method of waterborne epoxy floor coating

    CN110885615A

  • Metal surface anti-oil nano coating agent and preparation method thereof

    CN114702871A

  • Botton-surface combined type antifouling and antiseptic nanometer polysiloxanes coating and preparation method thereof

    CN106479354A